2015
DOI: 10.3122/jabfm.2015.s1.150042
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Behavioral Health and Primary Care: Consulting, Coordinating and Collaborating Among Professionals

Abstract: Purpose: This paper sought to describe how clinicians from different backgrounds interact to deliver integrated behavioral and primary health care, and the contextual factors that shape such interactions.Methods: This was a comparative case study in which a multidisciplinary team used an immersioncrystallization approach to analyze data from observations of practice operations, interviews with practice members, and implementation diaries. The observed practices were drawn from 2 studies: Advancing Care Togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 58 publications
0
74
0
Order By: Relevance
“…22 Access to a consulting psychiatrist could help keep the care of moderate to higher-need patients in the practice. Table 3 shows the majority of federally qualified health centers (FQHCs), FQHC-CMHCs, CMHC, and health system, government and hospital-owned practices were able to establish access to a consulting psychiatrist, and most privately owned primary care practices were not.…”
Section: Establishment Of Continuum Of Care Pathways For Patientsmentioning
confidence: 99%
“…22 Access to a consulting psychiatrist could help keep the care of moderate to higher-need patients in the practice. Table 3 shows the majority of federally qualified health centers (FQHCs), FQHC-CMHCs, CMHC, and health system, government and hospital-owned practices were able to establish access to a consulting psychiatrist, and most privately owned primary care practices were not.…”
Section: Establishment Of Continuum Of Care Pathways For Patientsmentioning
confidence: 99%
“…Cohen et al 18 describe the use of consulting, coordinating, and collaborating as approaches depending on the clinical task. Huddles or other structured or unstructured meetings can be used to plan care on an ongoing basis, with interprofessional complex care meetings to focus on patients with more difficult issues.…”
Section: Care Processes and Structuresmentioning
confidence: 99%
“…Practices such as those found in this special issue have shown that in the face of profound barriers, they can successfully integrate care and build their own case for why we integrate. 8,9 These practices further the cause. They work to change the historically fragmented lens in which we view health.…”
mentioning
confidence: 99%